2018
DOI: 10.1007/s00415-018-9047-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in a German cohort of Parkinson’s patients assessed with three different measures

Abstract: The associations between clinical aspects of PD and QoL vary substantially among all three measures. Importantly, depression as a frequent comorbidity in PD is underestimated by the EQ-5D, but not by the PDQ-39 and the WHOQOL-100/WHOQOL-BREF. In turn, motor impairments are underestimated by the latter and associated strongest with QoL in the EQ-5D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…Despite these results, studies including patients in more advanced stage of PD are still needed for a better understanding of this relationship. Balzer-Geldsetzer et al (2018) also observed relationship between higher MI assessed by the HY scale and worse global quality of life as well as in some of the domains of quality of life (i.e., mobility, activities of daily live, emotional well-being, cognition, and communication domains) in patients with mild to moderate PD. However, although previous studies (He et al, 2016;Rosqvist et al, 2021) have also observed relationship between higher MI and worse global quality of life in patients with advanced PD, they did not assess the different domains of quality of life.…”
Section: Introductionmentioning
confidence: 62%
“…Despite these results, studies including patients in more advanced stage of PD are still needed for a better understanding of this relationship. Balzer-Geldsetzer et al (2018) also observed relationship between higher MI assessed by the HY scale and worse global quality of life as well as in some of the domains of quality of life (i.e., mobility, activities of daily live, emotional well-being, cognition, and communication domains) in patients with mild to moderate PD. However, although previous studies (He et al, 2016;Rosqvist et al, 2021) have also observed relationship between higher MI and worse global quality of life in patients with advanced PD, they did not assess the different domains of quality of life.…”
Section: Introductionmentioning
confidence: 62%
“…However, female gender proved to be a negative predictor for physical-functioning and socioemotional HrQoL, whereas male gender mainly affected the HrQoL cognition domain. Conversely, in a prospective study on a cohort of patients with idiopathic PD in Germany, female patients reported more problems in all dimensions, except selfcare [40]. At the same time, a longitudinal study designed to analyze the effect of PD onset on life satisfaction showed marked reduction of life satisfaction among individuals in the second half of life in men, but not in women [41].…”
Section: Quality Of Lifementioning
confidence: 88%
“…In addition, some studies found that REM sleep behavior disorder with reduced striatal dopamine transporter values and increased expression of PD‐related pattern may be associated with the occurrence of PD 65‐67 . The discrepancy between studies could be partly due to differences in instruments, 68,69 sampling methods, disease severity, 14,70 effects of treatments, 71‐75 cognitive performance, 76 and clinical presentations caused by different associated genes 77 . The limited number of studies with the same QOL measure precluded an analysis of the moderating effects of the abovementioned demographic and clinical characteristics on QOL in PD.…”
Section: Discussionmentioning
confidence: 99%